Financing innovation - William R. Kerr; Ramana Nanda (Bank of Finland, 2015)
We review the recent literature on the financing of innovation, inclusive of large companies and new startups. This research strand has been very active over the past five years, generating important new findings, questioning some long-held beliefs, and creating its own puzzles. Our review outlines the growing body of work that documents a role for debt financing related to innovation. We highlight the new literature on learning and experimentation across multi-stage innovation projects and how this impacts optimal financing design. We further highlight the strong interaction between financing choices for innovation and changing external conditions, especially reduced experimentation costs.
URN:NBN:fi:bof-201512141480
Keywords: G21; G24; L26; M13; O31; O32; 330